Does historical fiscal capacity leave a long-lasting legacy? Evidence from TV tax evasion - Luca Bagnato (University of Zurich, Department of Economics, 2022)
In this paper I study whether citizens' tax morale (and, more broadly, citizens' attitudes towards the state) can be affected by past institutions, focusing on the role of historical fiscal capacity. Exploiting the features of the tax collection system of a pre-unification state in XIX Century Italy I identify differences in local historical fiscal capacity (as proxied by geographical proximity to a tax collector) and map them into contemporary tax morale, as measured by evasion of the TV Tax in 2014. Exploiting only variation in historical fiscal capacity that arises within matched pairs of neighbouring towns on the border of tax districts, I find imprecisely estimated and arguably small differences in tax morale today between towns where fiscal capacity was different. Investigating the mechanisms of transmission, I provide evidence that phenomena associated with structural transformation are likely to have halted the persistence of the historical fiscal capacity effect.
Keywords: D73; D91; N43; H26; 330; Fiscal capacity; Tax collection; Tax evasion; Tax morale; TV tax; Italy